Performance of Bhote type garlic genotypes under Karnali region of Nepal - Giri, Raj Kumar; Chalise, Basant; Paneru, Pragati Babu; Subedi, Giri Dari; Poudel, Bishwash; Regmi, Homan; Rana, Lokendra; Khadka, Dinesh; Kathayat, B.D.; Budha, Chandra (Journal of Agriculture and Environment, 2018)
Advance Yield Trial on different Bhote type garlic genotypes collected from different districts of Nepal was carried out at Horticultural Research Station, Rajikot, Jumla for two consecutive years 2013/14 and 2014/15 to evaluate garlic genotypes suitable for the Karnali region of Nepal. Minimal work has been done in past on garlic, almost all of which centered at terai and mid hills that's why this study was carried out to select suitable bhote type garlic genotypes for high hill. Eleven different garlic genotypes were tested on Randomized Complete Block Design (RCBD) with three replication. Tested genotypes differed significantly for vegetative as well as yield parameters. During 2013, the highest bulb yield (47.41 t/ha) was recorded from ARM 01 followed by Mugu Local (47.01 t/ha), ARM 04 (46.98 t/ha), Kathmandu Local (45.41 t/ha), Chinese (37.91 t/ha) and the lowest from ARM 08 (20.1 t/ha). Similarly, during 2014/15, the highest bulb yield was observed from ARM 01 (50.32 t/ha) followed by Mugu Local (49.91 t/ha), Kathmandu Local (41.62 t/ha), Chinese (29.60 t/ha) and the lowest from ARM 05 (12.51 t/ha). Based on the average result of both years, ARM 01, Mugu Local, Kathmandu Local, ARM 04 and Chinese showed the better productivity ranged from 29.6 t/ha to 50.32 t/ha which are the promising garlic genotypes for the Karnali region of Nepal.